Changes in the US financial system and the subprime crisis - Jan Kregel (Levy Economics Institute of Bard College, 2008)
This paper traces the evolution of housing finance in the United States from the deregulation of the financial system in the 1970s to the breakdown of the savings and loan industry and the development of GSE (government-sponsored enterprise) securitization and the private financial system. The paper provides a background to the forces that have produced the present system of residential housing finance, the reasons for the current crisis in mortgage financing, and the impact of the crisis on the overall financial system.
Keywords: E12; E32; E58; E63; 330; Financial Instability; Mortgage Finance; Subprime Mortgages; U.S. Financial System